Bangladesh : More and Better Jobs to Accelerate Shared Growth and End Extreme Poverty - World Bank Group (World Bank, Washington, DC, 2015)
Situated in a fertile low-lying river delta, Bangladesh combines high vulnerability to floods, tropical cyclones, earthquakes, and climate change with one of the world’s highest population densities, with around 159 million people living in less than 150,000 sq. km. With the world’s second lowest per capita income in 1975, it was labeled ‘the test case for development’ in view of the formidable development challenges it faced. Nevertheless, Bangladesh has proven to be remarkably resilient, developing well beyond initial expectations, and has made very good progress with poverty reduction. GNI per capita has grown from around US$100 in 1972 to US$1,314 in 2015, and the country crossed the World Bank threshold for the lower-middle-income group in 2015. As highlighted in the Seventh Five Year Plan background paper on ending extreme poverty, the agricultural labor market in Bangladesh tightened significantly in the decade of 2000s, which led to an increase in the real agricultural wage rate. Three main channels were the primary contributors: (a) relocation of farm labor to rural non-farm sectors; (b) relocation of rural labor to urban activities through the ‘pull effects’ of urbanization, creating employment opportunities for the extreme poor in labor-intensive construction and transport activities; and (c) jobs for the poor created in the manufacturing sector. Robust inflows of remittances from overseas workers contributed to spurring the creation of non-farm employment opportunities in rural areas.